IMPROVING MATERNAL NUTRITION THROUGH COMMUNITY GARDENS AND LOCAL FOOD EMPOWERMENT IN REMOTE AREAS - Asni Hasanuddin; Auliyah Imtiyaz Putri Mentari; La Ode Asrianto (JOURNAL OF COMMUNITY DEDICATION, 2026)
This study aims to examine in-depth the role of community gardens and local food empowerment in improving maternal nutritional status in remote areas through a literature review approach. Maternal nutritional issues, particularly in areas with limited access to nutritious food, remain a significant challenge in efforts to improve public health. Through a review of relevant scientific sources, articles, and policy reports, this study highlights how community garden initiatives and the optimization of local food sources can increase the availability, diversity, and consumption of nutritious food for pregnant and breastfeeding women. The study results indicate that community gardens serve not only as an alternative food source but also as a means of nutrition education, strengthening social solidarity, and enhancing community-based food security. Empowering women in local garden management has been shown to strengthen their role as agents of change within families and communities, promoting healthy eating behaviors, and reducing the risk of maternal malnutrition. This study emphasizes the importance of a participatory and locally-based approach to nutrition interventions, particularly in areas facing geographic and economic barriers. Therefore, integrating local health and agricultural policies that support the sustainability of community gardens and access to nutritious food is a key recommendation for strengthening maternal nutritional security in remote areas.